The p.Cys169Tyr variant of connexin 26 is not a polymorphism. - Zonta, Francesco; Girotto, Giorgia; Buratto, Damiano; Crispino, Giulia; Morgan, Anna; Abdulhadi, Khalid; Alkowari, Moza; Badii, Ramin; Gasparini, Paolo; Mammano, Fabio (Hum Mol Genet, 2015)
Mutations in the GJB2 gene, which encodes the gap junction protein connexin 26 (Cx26), are the primary cause of hereditary prelingual hearing impairment. Here, the p.Cys169Tyr missense mutation of Cx26 (Cx26C169Y), previously classified as a polymorphism, has been identified as causative of severe hearing loss in two Qatari families. We have analyzed the effect of this mutation using a combination of confocal immunofluorescence microscopy and molecular dynamics simulations. At the cellular level, our results show that the mutant protein fails to form junctional channels in HeLa transfectants despite being correctly targeted to the plasma membrane. At the molecular level, this effect can be accounted for by disruption of the disulfide bridge that Cys169 forms with Cys64 in the wild-type structure (Cx26WT). The lack of the disulfide bridge in the Cx26C169Y protein causes a spatial rearrangement of two important residues, Asn176 and Thr177. In the Cx26WT protein, these residues play a crucial role in the intra-molecular interactions that permit the formation of an intercellular channel by the head-to-head docking of two opposing hemichannels resident in the plasma membrane of adjacent cells. Our results elucidate the molecular pathogenesis of hereditary hearing loss due to the connexin mutation and facilitate the understanding of its role in both healthy and affected individuals.
Keywords: Alleles; Amino Acid Substitution; Cell Line; Connexins; Female; Gap Junctions; Gene Expression; Genotype; Hearing Loss; Humans; Immunohistochemistry; Male; Models, Molecular; Mutation, Missense; Pedigree; Polymorphism, Genetic; Protein Conformation; Protein Interaction Domains and Motifs; Transfection

PSIP1/LEDGF: a new gene likely involved in sensorineural progressive hearing loss. - Girotto, Giorgia; Scheffer, Deborah I; Morgan, Anna; Vozzi, Diego; Rubinato, Elisa; Di Stazio, Mariateresa; Muzzi, Enrico; Pensiero, Stefano; Giersch, Anne B; Corey, David P; Gasparini, Paolo (Sci Rep, 2015)
Hereditary Hearing Loss (HHL) is an extremely heterogeneous disorder. Approximately 30 out of 80 known HHL genes are associated with autosomal dominant forms. Here, we identified PSIP1/LEDGF (isoform p75) as a novel strong candidate gene involved in dominant HHL. Using exome sequencing we found a frameshift deletion (c.1554_1555del leading to p.E518Dfs*2) in an Italian pedigree affected by sensorineural mild-to-moderate HHL but also showing a variable eye phenotype (i.e. uveitis, optic neuropathy). This deletion led to a premature stop codon (p.T519X) with truncation of the last 12 amino acids. PSIP1 was recently described as a transcriptional co-activator regulated by miR-135b in vestibular hair cells of the mouse inner ear as well as a possible protector against photoreceptor degeneration. Here, we demonstrate that it is ubiquitously expressed in the mouse inner ear. The PSIP1 mutation is associated with a peculiar audiometric slope toward the high frequencies. These findings indicate that PSIP1 likely plays an important role in HHL.